Association Between Door to Balloon Time and Reperfusion with Left Ventricular Function and Heart Failure in Patients With ST Segment Elevated Myocardial Infarction Treated with Primary Percutaneous Intervention - Taha, Muhammad; Ahmad, Sajjad; Javeed, Muhammad; Kamran, Muhammad; ., Hamayon; Din, Syed Jalal Ud (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the association between prolonged D2B time and heart failure in patients with STEMI treated with primary PCI. Study Design: Prospective longitudinal study Place and Duration of Study: Cardiology department of Punjab Institute of Cardiology, Lahore Pakistan, from Oct 2024 to Feb 2025. Methodology: This study was carried out on 120 patients diagnosed with acute STEMI undergoing primary PCI after taking informed consent. Data was collected using pre-designed proforma. Patients were categorized into two groups based on door-to-balloon time, to compare the incidence of heart failure at 48 hours post-PCI. Relative risk was calculated, and data analysis was performed using SPSS version 26, with p-value <0.05 considered significant. Results: Heart failure was observed in 23% exposed patients vs. 15% non-exposed patients, relative risk of heart failure in exposed group was 1.556 (95% CI: 0.730–3.317). Conclusion: This study suggests that prolonged door-to-balloon time is linked to higher frequency of heart failure in patients with STEMI undergoing primary PCI, with relative risk indicating increased likelihood of heart failure in those with delayed intervention.